2023
DOI: 10.3390/nano13030406
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Insight of Charge Transport in BaTiO3/Epoxy Composites

Abstract: Space charge accumulation greatly influences the dielectric performance of epoxy composites under high voltage. It has been reported that nano-fillers can suppress the charge accumulation in the bulk of insulation materials. However, it is still unclear how the nano-fillers influence the charge distribution at the interface between the filler and polymeric matrix. In this work, the dielectric properties and the local dynamic charge mobility behavior at the interface of barium titanate/epoxy resin (BTO/EP) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Cu 2 + and Fe 3 + bications are present in CuFe 2 O 4 nanoparticles in octahedral and tetrahedral orientations, accordingly CuFe 2 O 4 nanoparticles can interact with PANI because PANI's nitrogen atoms interact with the metal ions in CuFe 2 O 4 via their lone pairs 39 . The electrostatic bonding between charge entities on the surface of copper ferrite and the charged group of PANI might end up in larger dielectric constants and the production of stable composites 40 . Thus, these films may be used as the electrode for asymmetric super capacitor similar to the asymmetric super capacitor reported by Priyanka et al using CuFe 2 O 4 ‐rGO nanocomposite 41 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu 2 + and Fe 3 + bications are present in CuFe 2 O 4 nanoparticles in octahedral and tetrahedral orientations, accordingly CuFe 2 O 4 nanoparticles can interact with PANI because PANI's nitrogen atoms interact with the metal ions in CuFe 2 O 4 via their lone pairs 39 . The electrostatic bonding between charge entities on the surface of copper ferrite and the charged group of PANI might end up in larger dielectric constants and the production of stable composites 40 . Thus, these films may be used as the electrode for asymmetric super capacitor similar to the asymmetric super capacitor reported by Priyanka et al using CuFe 2 O 4 ‐rGO nanocomposite 41 …”
Section: Resultsmentioning
confidence: 99%
“…39 The electrostatic bonding between charge entities on the surface of copper ferrite and the charged group of PANI might end up in larger dielectric constants and the production of stable composites. 40 Thus, these films may be used as the electrode for asymmetric super capacitor similar to the 41 It is crucial to know about loss factor of a material in order to find its electrical efficiency for various applications. In Ramesan et al 42 study, they showed the dielectric loss was nearly 2.25 for pure PANI.…”
Section: Electrical Analysismentioning
confidence: 99%
“…It is observed that a rise in temperature leads to a decrease in trap depth along with an increase in trap density 38,39 . Moreover, the incorporation of h‐BN and PDA interface between micro‐BST and EP introduces deep traps to inhibit the migration of charge carriers 40 . At temperatures above the curie point, while trap density for composites increases with rising temperature, the decrease in trap depth is minimal, which facilitates the trapping of charge carriers.…”
Section: Resultsmentioning
confidence: 99%
“…[56,73,74] In recent years, the probe microscopy method has enabled atomic-level resolution imaging, making it possible to study charge behaviors at the submicron scale. [75][76][77][78][79] Kelvin probe force microscopy (KPFM) is a technique used to measure the potential difference between a sample and the tip. [79,80] KPFM measures the work function between the tip and the surface as a function of potential difference.…”
Section: Introductionmentioning
confidence: 99%